Development of Guiding Cane with Voice Notification for Visually Impaired individuals - Emeline C. Guevarra; Marck Ivan Reyes Camama; Geonel Villanueva Cruzado (Institute of Advanced Engineering and Science, 2018)
Navigation in the physical environment is a challenge for those people who have very limited sense of sight or no vision at all. Assistive technologies for blind mobilization is not new and always have a room for improvement. Moreover, these assistive devices are limited in terms of its sensing and feedback abilities. This paper presents a microcontroller-based guiding stick capable of detecting several conditions of the environment such as obstacles in front, left and right positions of the user and detects ascending and descending staircases. The feedback is delivered by an audio output which dictates the direction to go or what condition the sensor detects in front of the user. Technical evaluation proves that the device was functional in terms of its accuracy, responsiveness and correctness. On the other hand, in the actual evaluation of the device with the visually impaired individuals, the device did not perform efficiently. It was also found that the device has the potential to be used effectively by the visually impaired who acquired their blindness in later stage of their life provided that they will have a proper training in using the device while navigating in the physical environment.